Characterization of fossil remains using XRF, XPS and XAFS spectroscopies - Zougrou, I.M. (2016)
Synchrotron radiation micro-X-Ray Fluorescence (m-XRF), X-ray photoelectron (XPS) and X-ray Absorption Fine Structure (XAFS) spectroscopies are applied for the study of paleontological findings. More specifically the costal plate of a gigantic terrestrial turtle Titanochelon bacharidisi and a fossilized coprolite of the cave spotted hyena Crocuta crocuta spelaea are studied. Ca L2,3-edge NEXAFS and Ca 2p XPS are applied for the identification and quantification of apatite and Ca containing minerals. XRF mapping and XAFS are employed for the study of the spatial distribution and speciation of the minerals related to the deposition environment.